Assessment of improvement of trainee surgical skills in the operating room for tonsillectomy. (11th March 2013) - Ahmed, Aadil; Ishman, Stacey L.; Laeeq, Kulsoom; Bhatti, Nasir I.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To determine the feasibility, reliability, and validity of an objective surgical assessment tool designed to measure the development of tonsillectomy skills by resident trainees in the operating room. A tonsillectomy evaluation instrument created previously serves as a basis for this tool, which incorporates many similar concepts but was optimized to maximize feasibility and reliability with simplified anchors and inclusion of global and task‐specific sections. Study Design Prospective longitudinal validation study. Methods Faculty input via modified Delphi technique was used to develop a new objective structured assessment of technical skills–based instrument for tonsillectomy. The task‐specific checklist (TSC) and global rating scale (GRS) measured tonsillectomy technical skills and overall surgical performance, respectively. Twenty‐one otolaryngology–head and neck residents (ranging from postgraduate year 1 to 6) were evaluated for a period of 3 years by 11 faculty members. Results Eighty‐three evaluations were completed showing strong correlation between both instruments (r = 0.95, P < .001). Our tool demonstrated construct validity for both TSC and GRS, showing higher scores with increasing surgical experience. Both instruments showed high interitem reliability with Cronbach α coefficients of 0.97 for both parts. Conclusions This assessment tool is a feasible, reliable, and valid instrument for the assessment of surgical competency in tonsillectomy. It is effective in providing structured feedback at the end of each procedure, which encourages specific, targeted development. Laryngoscope, 2013